Corporate governance, corporate social responsibility and performance with the moderating role of board equity ownership: Evidence from Indonesia’s oil palm companies - Asna, Asna (Advances in Social Sciences Research Journal, 2020)
The Oil Palm Companies is one of the highest contributions towards Indonesia economic development. However, the company performance in the oil palm companies is far from expectation which is related to how they responsible on their shareholders as well as stakeholders. Thus, the study purpose is to examine the relations between corporate governance mechanisms, corporate social responsibility and board equity ownership on performance in Indonesia’s Oil Palm Companies. The findings highlight a positive relationship between board equity ownership, corporate social responsibility and company performance. Furthermore, the moderating role of board equity ownership has a significant positive on the relationship between independence director and company performance as well as corporate social responsibility. The relationship between female director and company performance shows the same result with the interaction of board equity ownership. Currently studies have found that corporate governance mechanisms, corporate social responsibility have significant effect on company performance. Nevertheless, this evidence showed that direct relationship between corporate governance, social responsibility and company performance have mix results. Admittedly, the indirect relationship revealed that board equity ownership contributes significant effect on the relations between corporate governance, social responsibility and company performance particularly in Indonesia’s oil palm companies. Based on the author knowledge, a few studies have been done in oil palm companies which it provides a prominent issue in corporate governance mechanism particularly on board equity ownership which majority is held by family member ownership. Keywords Corporate governance, social responsibility, board equity ownership, company performance